2019
DOI: 10.1021/acsami.9b14951
|View full text |Cite
|
Sign up to set email alerts
|

Robust Photoelectrochemical Oxygen Evolution with N, Fe–CoS2 Nanorod Arrays

Abstract: Photoelectrochemical water splitting is a promising approach to enhance the efficiency of water splitting. However, it is still challenging to develop an efficient oxygen evolution reaction (OER) electrocatalyst that can be coupled with light due to inefficient light utilization. Here, we demonstrate that N, Fe-co-doped CoS 2 (N, Fe−CoS 2 ) nanorod arrays can act as a highly efficient photo-coupled electrochemical OER catalyst. In dark conditions, the N, Fe-doped CoS 2 on selfsupported stainless steel (SS) mes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 51 publications
1
22
0
Order By: Relevance
“…[ 32,33 ] Compared with metal‐based molecular cocatalysts, non‐photoresponsive metal oxides, such as RuO 2 and IrO 2 , are alternative oxidation cocatalysts with low resistivity and high corrosion resistance. [ 34–36 ] Therefore, we can expect that the deposition of metal oxides cocatalysts onto the sidewalls of 1D metal sulfide structure can effectively transfer multiple holes from sulfide to oxidation cocatalysts sites, which is indispensable for water oxidation.…”
Section: Figurementioning
confidence: 99%
“…[ 32,33 ] Compared with metal‐based molecular cocatalysts, non‐photoresponsive metal oxides, such as RuO 2 and IrO 2 , are alternative oxidation cocatalysts with low resistivity and high corrosion resistance. [ 34–36 ] Therefore, we can expect that the deposition of metal oxides cocatalysts onto the sidewalls of 1D metal sulfide structure can effectively transfer multiple holes from sulfide to oxidation cocatalysts sites, which is indispensable for water oxidation.…”
Section: Figurementioning
confidence: 99%
“…In Figure 4 c, peaks located at 55.7 and 54.2 eV are attributed to Se 3d 3/2 and Se 3d 5/2 , respectively, close to the previously reported values of Se doped CoS 2 . 53 And the broad peak located at 59.7 eV corresponds to the surface oxidation of the Se edges. 26 High-resolution spectra of S 2p shown in Figure 4 d can be decomposed into three peaks, locating at 162.8 and 163.9 eV, assigned to S 2p 3/2 and S 2p 1/2, respectively, and locating at 168.9 eV, assigned to S surface oxide contamination in Se–CoS 2- x .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that moderate doping can effectively improve the electrochemical catalytic activities, e.g., N, 39−45 P, 46−50 Ni, 51 Fe, 52,53 Al, 54 Se, 55 Mn, 56 and so on. Therein, the performances of selenide products are much better than those of other products (e.g., sulfur), which may be ascribed to the following reasons: performances of electrochemical catalytic devices.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considerable attention has been devoted to two-dimensional (2D) materials as promising functional materials, in particular to transition metal dichalcogenides (TMDCs) [ 1 , 2 , 3 , 4 ], due to rapid advances in synthesis, transfer, spectroscopic detection, and manipulation. Since 2D TMDCs have unique physicochemical properties such as high mobility, large surface area, and significant catalytic activities, they can be effectively used for efficient light harvesting, sensitive photo-detection, and catalytic conversion systems [ 5 , 6 , 7 , 8 ]. Among 2D TMDCs, particularly, tungsten disulfide (WS 2 ), with direct optical band gaps of 1.35 and 2.05 eV for bulk and monolayer structure, is of great interest due to its particular semiconducting behavior, intrinsic electrical conductivity, and electrocatalytic property when the number of layers is lower [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%